Proposta de eficientização energética do Laboratório de Engenharia Elétrica UFPA/Camtuc para obtenção da certificação segundo o Procel - PINTO, Gileno Américo (2018)
This paper aims to propose an energy efficiency of the Laboratory of Energy, Federal University of Pará-UFPA Campus Tucuruí, based on the technical requirements of the Quality Level of Energy Efficiency of Commercial Buildings, and Public Service (RTQ-C). The RTQC has three study requirements for certification label that is envelopment, Lighting System and Air Conditioning System The study of these three requirements will result in the overall classification of the building. You can however get the ranking of only one study requirements analysis and thus make for a partial classification of the building. This work focuses on analyzing and proposing improvements to the lighting system Electrical Engineering Laboratory - LEE, UFPa / CAMTUC, in which we sought to identify whether it meets the standards of the Brazilian Association of Technical Standards (ABNT), in order to get the National Energy Conservation Label (ENCE), issued by the National Institute of Metrology, Standardization and Industrial Quality (INMETRO). In the case of building study (LEE), does not meet standards of ABNT, the procedure will identify vulnerable points the rules and try to fit them in relation to them and then take the assessment through the relevant parameters that give us a result end and then it appears on the label what type of building under study correspond.